Вплив глобалізаційних процесів на професійно-правове становище молодого покоління - Жаровська, І.; Ортинська, Н.; Zharovska, I.; Ortynska, N. (СНУ ім. Лесі Українки, 2018)
У статті розглянуто особливості глобалізаційних змін, що мають вплив на всі сфери життя сучасної молодої людини. Проаналізовано шість основних підходів до освіти XXI століття. Проаналізовано вплив технологічного прогресу на ринок праці. У зв’язку із наявними змінами постає необхідність у зміні підходів до освіти загалом. Доведено, що освітні програми майбутнього повинні бути розраховані не на засвоєння матеріалу студентом, а на розвиток аналітичного, креативного мислення, що зможе знайти своє практичне застосування у майбутній професійній діяльності. The article discusses the features of the globalization changes that affect all aspects of modern youth life. The six main approaches to the education of the XXI century are analyzed: free access to education, investing in human resources, innovative technologies in teaching and learning, the value of learning itself, reconsidering the issues of leadership and counseling, bringing education closer to the consumer. Technological progress has caused disappearance of some professions. These changes have become an alarming signal for young people all over the world. Existing changes necessitated changes in approaches to education in general. The educational programs of the future should be designed not for mastering of the learning material by the student, but for the development of analytical, creative thinking that can find its practical application in the future professional activities. The author argues that it is more difficult for young people today to realize themselves in a competitive social environment. Therefore, the younger generation is forced to study throughout life, develop their creativity and analytical thinking, since no technologically perfect intelligence can match the human unlimited and all-encompassing mind.
Globalization Process Impact on the Professional and Legal Status of the Younger Generation
Keywords: глобалізація; молоде покоління; освіта; технологічний прогрес; штучний інтелект; globalization; young generation; education; technological progress; artificial intelligence